Symbolism in Wafak Containing Al-Quran Roland Barthes's Semiotic Perspective - Al-Banna, Muhammad Rif'at; Al-Fikri Ys, Irsyad (Hanifiya: Jurnal Studi Agama-Agama, 2023)
This article discusses research on symbolism in wafak containing the Koran in Muslim communities. Wafak has other derivations such as hizb, ruqyah, and amulet is the practice of prayer which is used as a means of endeavor for a servant to be more taqarrub to Allah SWT. The research method used is qualitative, with the type of research being library research. The results of this study are that the wafak of the Qur'an as a symbol of the form of a servant's endeavor to get closer to Allah SWT. In addition, wafak al-Quran can be justified in Islam by following several provisions, one of which is to believe that wafak cannot give any effect, but that can be realized only because of Allah's destiny alone and wafak is only one of the reasons.